The English Reformation and the laity : Gloucestershire, 1540-1580 - Litzenberger, C. J. (Cambridge studies in early modern British history., 1997)
This book examines the effects of the English Reformation on the full spectrum of lay religion from 1540 to 1580 through an investigation of individuals and parishes in Gloucestershire. Rather than focusing on either the acceptance of Protestantism or the demise of the traditional Catholic religion, as other historians have done, it considers all shades of belief against the backdrop of shifting official religious policy. The result is the story of responses ranging from stiff resistance to eager acceptance, creating a picture of the religion of the laity which is diverse and complex, but also layered as parishes and individuals expressed their faith in ways which reflected the institutional or personal nature of their piety. Finally, while the book focuses on Gloucestershire, it reveals broad patterns of beliefs and practices which could probably be found all over England.